Local Wisdom in Corporate Social Responsibility: Tri Parartha-Based Practices at the Village Credit Institution of Gelgel Customary Village, East Bali - Dewi, Cok Istri Ratna Sari; Triyuwono, Iwan; Hariadi , Bambang; Roekhudin (Universitas Udayana, 2025)
This study examines the practice of Corporate Social Responsibility (CSR) based on Tri Parartha—a Balinese moral philosophy emphasizing compassion (asih), giving (punya), and devotion (bhakti)—at the Village Credit Institution (LPD) of Gelgel customary village, Klungkung District, East Bali. Using an ethnomethodological approach, data were analyzed through indexicality (contextual meaning of expressions) and reflexivity (actors’ reasoning behind actions). The findings show that Tri Parartha shapes CSR practices as culturally embedded actions rather than responses to external mandates. Asih appears in environmental care, punya in support for vulnerable groups and youth, and bhakti in religious contributions. These practices reinforce mutual trust, community participation, and legitimacy. The study contributes to CSR theory by offering a culturally grounded alternative to dominant Western models, illustrating how local moral frameworks can sustain inclusive and resilient institutions. Tri Parartha-based CSR demonstrates that ethical business practices rooted in indigenous values can create a self-reinforcing cycle of social benefit and community empowerment.